Impact of silviculture system on regeneration status and species diversity: reflection from far-western lowland, Nepal - Ojha, Prakash; Acharya, Keshav Raj; Subedi, Aliza; Regmi, Siddhartha (Banko Janakari, 2023)
Adoption of silvicultural system aims to enhance the regeneration of desired species. Irregular shelterwood system was initiated in Shorea robusta dominated forest under different forest management regimes including community forest in lowland forest of Nepal. The present study was conducted in 2023 to compare the regeneration status and species diversity between the two different management practices (scientific forest management and conventional forest management) in Patela Community Forest in far-western lowland of Nepal. A total of 27 quadrat sample plots (each with 4 m2) were established at a spacing of 50 m x 50 m across the three scientifically managed blocks, each with an area of 2.14 ha. An equal number of sample plots (27) were established within the conventionally managed blocks. Important Value Index, Sorenson’s Similarity Indices, and the distribution patterns of each species were calculated in both the management blocks to compare the species diversity. Shapiro-Wilk test was performed to check the normality of regeneration count, and a two-sample t-test was employed to examine the significant differences in the mean count of the plant species. The present study revealed that the conventionally managed forest block has higher species diversity; however, the number of seedlings was significantly high in the scientifically managed forest blocks. The Important Value Index Analysis indicated that S. robusta was dominant tree species in both the management blocks followed by Terminalia tomentosa; however, there was higher number of S. robusta regeneration under the scientifically managed blocks. The study concludes that irregular shelter-wood system is effective for regulating S. robusta forests in the western lowlands of Nepal.